Efisiensi Produksi dan Skala Usaha Kelapa Dalam di Kabupaten Lampung Selatan - Irmayani Noer (Politeknik Negeri Lampung, 2010)
Coconut is an agriculture commodity which is has very important meaning for economic in North Lampung Recidence. Based on acreage, coconut plantation effort by the most of people traditional farming. This research was conduct to identify the factors which was influence coconut production and then to determine of return to scale coffee production. The factors wich was influence coconut production was analysis with Cobb-Douglas function and than this function to be restricedt to determine return to scale production of coconut. Input factor is acrea, labor, fertilizer, pesticide, the age of plant, knowledge and experiences of farmer. The analysis showed that production was influence factors acrea, fertilizer, pesticide, the age of plant, and experiences of farmers. Meanwhile, the knowledge factors is not significant to influeces of production. Return to scale analysis shows that condition of coconut production is increassing return to scle. It’s mean that if there were the production factors is increase, production will be increase more. Key words: Coconut, Production Efficiency and Return to Scale